A study on the legal rights of Indonesian workers in the Construction sector / Asrulna'im Abdullah, Ahmad Nusa and Noriana Mohamad Nazuir. - Abdullah, Asrulna'im; Nusa, Ahmad; Mohamad Nazuir, Noriana (Faculty of Law, 2009)
Malaysia is one of East Asia's greatest economic success stories. As the New Fxonomic Policy took shape, labour costs rose dramatically. The government eventually legalized the importation of foreign workers for the manufacturing, construction and service sectors. However, the vulnerable foreign workers are being deprived of their basic rights due to the lack of implementation of law which governs their rights. The scope of this study focuses on the Indonesian workers in the construction sector. This paper analyses and evaluates the current laws relating to the hiring of such foreign workers, the terms of their employment contracts and the safeguards provided in relation to their basic rights. Instances relating to the various deprivations of their basic human rights are highlighted. The objectives are to determine how the rights granted by Malaysian law to Indonesian construction workers can be better implemented and to provide awareness to both employer and employee. The approach adopted in this paper is based on a qualitative research approach and mainly library based.